The Effect of Fractional Carbon Dioxide Laser on Melanogenesis in Human Melanocytes and Vitiligo Mouse Models - Tang H; Ding X; Huang Y; Xu D; Fan Y (Dove Medical Press, 2024)
Hui Tang,1,* Xiaoxia Ding,2,3,* Youming Huang,2 Danfeng Xu,2 Yibin Fan1,2 1Graduate School of Clinical Medicine, Bengbu Medical College, Bengbu, 233030, People's Republic of China; 2Center for Plastic & Reconstructive Surgery, Department of Dermatology, Zhejiang Provincial People's Hospital, Affiliated People's Hospital of Hangzhou Medical College, Hangzhou, 310014, People's Republic of China; 3Department of Dermatology and Venereology, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, 325000, People's Republic of China*These authors contributed equally to this workCorrespondence: Yibin Fan, Graduate School of Clinical Medicine, Bengbu Medical College, Bengbu, 233030, People's Republic of China, Tel +86 18806538451, Email fanyibin@hmc.edu.cnIntroduction: Vitiligo is an acquired skin pigmentation disorder, the cause of which is poorly understood. Researchers in this field are dedicated to exploring novel treatments for achieving re-pigmentation.Methods: Mice were randomly selected and divided into control, model, and model+laser groups. Evaluate the impact of different levels of carbon dioxide laser irradiation on tyrosinase activity, melanocyte viability, and melanin content.Results: In this study, it was found that the cell viability and melanin content were significantly enhanced in human melanocytes after treatment with different energy densities of fractional carbon dioxide laser. In addition, laser-treated vitiligo mouse models showed mild pathological changes.Discussion: Therefore, we believe that fractional carbon dioxide laser may be a potential adjunctive modality for treating vitiligo.Keywords: vitiligo, fractional carbon dioxide laser, melanocytes, melanogenesis, vitiligo mouse models